Analisis Pengaruh Perceived Ease Of Use Dan Perceived Usefulness Terhadap Reuse Intention Dengan Customer Satisfaction Sebagaik Variabel Intervening (Studi Pada Penggunaan Aplikasi New Sakpole) - Kuswanadji, Arief; Kuswardani, DC; Utaminingsih, Adijati (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The Central Java Province's New Sakpole program allows for online motor vehicle tax (MVT) payments. The rationale behind selecting this item is that a growing number of taxpayers choose to pay MVT through the Office of Single Administrative System One Roof (Samsat), leaving the taxpayers who utilize this application rather rare. Furthermore, the new Sakpole app has a low rating in the Play Store and numerous comments expressing unhappiness. This study aims to analyze the impact of perceived usefulness and simplicity of use on the intention to reuse, with customer satisfaction acting as a mediating variable in the use of New Sakpole applications. Using the purposive sampling technique, 100 respondents who have used the New Sakpole application make up the study's sample. The SmartPLS program 3.0, which operates on computer media, is used in this study to analyze data.The test's findings demonstrated that customer satisfaction was significantly and favorably impacted by perceived usefulness and convenience of use. Additional research indicates that reuse intention is significantly and favorably influenced by perceived usefulness and simplicity of use. The mediation test's findings demonstrated that customer satisfaction has the power to mediate the relationship between perceived usefulness and convenience of use and reuse intention.